Genetic data of 15 autosomal STR loci: an analysis of the Araraquara population colonization (São Paulo, Brazil) - Martins, Joyce Aparecida [UNESP]; Figueiredo, Raquel de Freitas [UNESP]; Yoshizaki, Cyntia Sumie [UNESP]; Paneto, Greiciane Gaburro [UNESP]; Cicarelli, Regina Maria Barretto [UNESP] (Springer, 2011)
The genetic markers most commonly utilized to determine identity and in paternity testing are autosomal short tandem repeats (STRs); to interpret the DNA analysis, the results of a case have to be compared with a pertinent reference population. Thus, the aim of this work was to characterize the genetic profile of the population of Araraquara (So Paulo, Brazil) by analyzing 15 STR loci included in the PowerPlex(A (R)) 16 System and to correlate these data with the migration history of the population. No deviations from the Hardy-Weinberg equilibrium were observed for any of the loci, after Bonferroni's correction. Forensic parameters exhibited high values, the most polymorphic loci being Penta E, D18S51 and FGA. An unweighted pair-group method with arithmetic mean (UPGMA) tree based on genetic distances showed that the current population of Araraquara is grouped with populations of the southeastern region of Brazil, which are close to the European group but distant from African and Amerindian populations. Estimates of admixture components revealed that the contributions to the population of Araraquara were 76% European, 18% African, and 6% Amerindian.
Keywords: STR; Allele frequencies; PowerPlex (R) 16 System; Araraquara; Brazil